Generative Artificial Intelligence and its role in mitigating Foreign Language Speaking Anxiety - Alwreikat, Emad (Research Journal in Advanced Humanities, 2026)
Generative Artificial Intelligence (GenAI) has emerged as a transformative tool in language pedagogy, particularly in mitigating Foreign Language Speaking Anxiety (FLSA). By offering interactive, judgment-free environments, GenAI lowers psychological barriers and socio-evaluative threats inherent in traditional classrooms (Xiao et al., 2025; Mandasari & Oktaviani, 2018). Research indicates that AI-powered chatbots and adaptive platforms enhance the educational experience through personalized support and real-time feedback, fostering learner autonomy and linguistic precision (Klimova et al., 2023; Lee, 2023). However, concerns persist regarding the authenticity of AI interactions and their long-term motivational impact, highlighting the need for a balanced integration with traditional methodologies (Horwitz et al., 1986; Messick, 1989). Challenges such as digital literacy, ethical considerations of content ownership, and learner preferences for human evaluation in high-stakes contexts further complicate this transition (Creswell, 2020). Ultimately, the strategic deployment of GenAI is poised to reshape language acquisition trajectories by harmonizing technological innovation with essential psychological support (Abdul Aziz & Kashinathan, 2021; Horwitz, 2020).